Program CSR PT BANK RAKYAT INDONESIA, TBK Dalam Memperbaiki Kualitas Lingkungan Hidup Indonesia - Syarief, Fauzi (Jurnal Public Relations (J-PR), 2020)
This research is a research on how to use SWOT analysis in an organization's Corporate Social Responsibility strategy. The formulation of the problem in this study is "How is the Corporate Social Responsibility of PT Bank Rakyat Indonesia in the CSR Program". The method used is SWOT analysis and using qualitative descriptive research methods. By providing a matrix for the discussion, it was found that an organization could first analyze the organization's internals and could find a description of the problem in increasing visitor interest.